Pengaruh Variasi Bukaan Lubang Dan Model Penampang Lubang Pada Bangunan Pintu Air Kombinasi Ambang Saluran Terbuka Lahan Pasang Surut - Rangga Saputra Pratama; Siswanto Siswanto; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The influence of rising sea water on tidal land has always been a very common problem in the process of tidal land use as farmland. Network system of water began to be developed, namely the open channel system comes with water as formatter building floodgates, but it hasn't been able to made a solution of the problem increases in sea water to agricultural areas. The importance of knowing the description of the behavior of the flow on the draft water building make this research needs to be done. The use of open channels that come with building a sluice water regulator combined with water weirs are expected to hamper the rising tide if applied on tidal land use as farmland. The purpose of this research is to know the influence of variations of the opening hole sluice and sluice hole cross-section shape of the flow behavior change through the door water combined with weirs in open channel water in the form of discharge coefficient value (Cd). This research was conducted at the Laboraturium University of Hidroteknik Riau using a flume which features open channel water balance door and threshold. The results of this research show that building floodgates open channel on the threshold and are able to withstand the tide of different variations of the opening hole. The value of the coefficient of discharge (Cd) 10 mm hole openings variations between 0.60-0.70, 20 mm hole openings variations i.e. 0.30-0.45 and a 30 mm hole openings variations i.e. 0.25-0.40, These results are obtained from multiple upstream water faces tall test channel.Keywords : open flow, the floodgates, the coefficient of discharge.